The Implementation of the Green School Model in Shaping Sustainable Lifestyles - Eni Veronika; Ahmad Yani T (CV. Publikasi Indonesia, 2024)
The problem with the green school program implemented in schools is that it has not yet been integrated into the curriculum or teaching materials, resulting in its limited impact on students. Teachers often feel concerned about addressing waste issues, maintaining school cleanliness, and selecting beneficial plants for the school, as they are the spearhead of the green school initiative. This research is qualitative with a case study strategy, this training employs lectures, discussions, and Focus Group Discussions (FGD). The initial evaluation results indicate a low level of understanding among teachers and students regarding their roles and responsibilities in supporting the green school initiative. This lack of understanding stems from the belief among teachers and students that waste management and school environment maintenance are the responsibilities of the principal and the government. After receiving training and undergoing evaluation, both teachers and students began to understand the roles and functions they could play in helping the school implement the green school initiative. Their enthusiasm for the training resulted in a high level of understanding of their roles in carrying out the green school program at SMP AMKUR Bengkayang, Bengkayang Regency.